Evaluation De La Dégradation De La Chamaeropaie Du Versant Sud Du Mont « jbelLakraa » (Maroc) Etudes Floristique Et Morphométrique - Khalid Benarchid; Mohammed Khatori; Said Hilali (European Scientific Journal, ESJ, 2018)
Our study is devoted to the chamaeropaie degradation assessment of the jbel Lakraa southern slope, located in the northern Middle Atlas in the Ribat Al Khair region. The floristic study revealed a specific richness of 124 species belonging to 95 genera and 33 vascular plants families, as well as a specific diversity relatively high with a Shannon-Weaver index of 3.88. A relatively high specific diversity with a Shannon-Weaver index of 3.88 was observed. However, the floristic composition showed a disturbance expressed by the index of equitability which is 0.58 and a strong therophytisation of 63% with a very high perturbation index of 69%. This disturbance is also illustrated by the toxic or spiny species proliferation such as Asphodelus ramosus, Drimia maritima and Scolymus hispanicus. The morphometric study was carried out on two strata (stratum 1 anthropized - stratum 2 wooded). The Statistical analysis showed that the diameter and height of the foliage, as well as the number of leaves per individual of the tree stratum are significantly higher than those of the anthropized stratum. Furthermore, an absence of correlations between the morphometric variables was recorded in the anthropized stratum. The chamaeropaie degradation state is alarming as indicated by the floristic and morphometric results, urgent measures must be taken to regulate its exploitation and preservation.